Hubungan Faktor Sosiodemografis dengan Sikap Keluarga dalam Mendampingi Pasien Menjelang Ajal - Thifal Fairuz Megumi; Sheizi Pristasari; Hasniatisari Harun; Hartiah Haroen (Universitas Malahayati Lampung, 2026)
ABSTRACT Family involvement is an essential component in the care of terminal patients, particularly during palliative care andthe end-of-life phase. Family attitudes toward accompanying terminal patients may be influenced by various factors, including sociodemographic characteristics. This study aimed to analyze the relationship between sociodemographic factors and family attitudes in accompanying terminal patients at the end of life. This study employed a quantitativecross-sectional design and involved 66 respondents selected through purposive sampling. Family attitudes were measured using the Indonesian version of the Frommelt Attitudes Toward Care of the Dying Form B (FATCOD-B-I). Data were analyzed using univariate and bivariate analyses with the Chi-Square test, along with alternative tests suchas the Likelihood Ratio or Fisher’s Exact Test when Chi-Square assumptions were not met. A total of 54.5% of respondents demonstrated a favorable attitude toward accompanying terminal patients at the end of life. Bivariate analysis indicated that sociodemographic factors were not significantly associated with family attitudes toward end-of-life caregiving (p 0.05). Family attitudes toward accompanying terminal patients were not significantly associated with sociodemographic factors. Psychological, experiential, and psychosocial-spiritual factors may play amore influential role. Keywords: End-Of-Life Care, Family, FATCOD-B-I, Palliative Care, Sociodemographic. ABSTRAK Pendampingan keluarga memegang peran penting dalam perawatan pasien terminal, terutama pada perawatan paliatif dan fase menjelang ajal. Sikap keluarga dalam mendampingi pasien terminal dapat Menganalisis hubungan antara faktor sosiodemografis dengan sikap keluarga dalam mendampingi pasien terminal menjelang ajal. Studi inimenggunakan desain kuantitatif dengan pendekatan cross-sectional. Penelitian melibatkan 66 responden yang dipilih menggunakan teknik purposive sampling. Sikap keluarga diukur menggunakan instrumen Frommelt Attitudes Toward Care of the Dying Form B versi Indonesia (FATCOD- B-I). Analisis data dilakukan secara univariat dan bivariat menggunakan uji Chi-Square, serta uji alternatif Likelihood Ratio atau Fisher’s Exact Test jika asumsi uji tidak terpenuhi. Sebanyak 54,5 persen responden menunjukkan sikap favorable dalam mendampingi pasien menjelang ajal.Analisis bivariat menunjukkan bahwa faktor sosiodemografis tidak memiliki hubungan yang bermakna secara statistikdengan sikap keluarga dalam mendampingi pasien terminal menjelang ajal dengan nilai p lebih dari 0,05. Sikapkeluarga dalam mendampingi pasien terminal menjelang ajal tidak berhubungan secara langsung dengan faktor sosiodemografis. Faktor lain seperti pengetahuan tentang perawatan paliatif, pengalaman pendampingan, serta dukungan psikososial dan spiritual kemungkinan lebih berperan dalam membentuk sikap keluarga. Kata Kunci: FATCOD-B-I, Keluarga, Menjelang Ajal, Perawatan Paliatif, Sosiodemografis.